Sexual selection on Drosophila serrata male pheromones does not vary with female age or mating status. (14th May 2014) - Gershman, S.; Delcourt, M.; Rundle, H. D.
Abstract Mate preferences are costly and are thought to evolve due to the direct and/or indirect benefits they provide. Such costs and benefits may vary in response to intrinsic and extrinsic factors with important evolutionary consequences. Limited attention has been given to quantifying such variation and understanding its causes, most notably with respect to the direction and strength of preferences for multivariate sexual displays. In Drosophila serrata, female preferences target a pheromone blend of long‐chain cuticular hydrocarbons (CHCs). We used a factorial design to test whether female age and mating status generated variation in the strength and direction of sexual selection on male CHCs. Replicate choice mating trials were conducted using young and old females (4 or 10 days post‐emergence) that were either virgin or previously mated. The outcome of such trials is known to capture variation in female mate preferences, although male–male interactions may also contribute. Directional sexual selection on male CHCs was highly significant within each treatment, but there was little evidence of any variation among treatments. The absence of treatment effects implies that the multivariate combination of male CHCs preferred by females was constant with respect to female age and mating status. To the extent that male–male interactions may also contribute, our results similarly imply that these did not vary among treatments groups. With respect to D. serrata mate preferences, our results suggest that either plasticity with respect to age and mating status is not beneficial to females, or preference expression is somehow constrained.